Políticas públicas urbanas, espaço público e segregação em Maringá-PR - Galvão, Altair Aparecido (2012)
Public spaces in Maringá are analyzed in the perspective of its general functioning, because the main objective of this research is to understand, from a geographic view, the production of the public space of Maringá, linking it to the field of domination and appropriation from the political action, to the capital storage and to the consequent reproduction of the social inequality. In this perspective, in its process of production and appropriation, it revealed the existence of a segmented sociability. The reflections were organized in three analytic levels: the politic domination, the capital stock and new ways of appropriation. The first two cases are connected to the field of domination, the first, dealing with the actions of public power and local choicest part and the second dealing with the process of stock and reproduction of capital. The third analytic level is focused on the recreation of public space, that is, the appropriation of new spaces that are used for everyday practices. It is exactly in this last level that reflections make possible the identification of perspectives of transformation of public space in the place of reproduction of different ideas of culture, leisure, rest among other things. For the accomplishment of this research, it was used the following methodological procedures: theoretical reference, empirical reference and technical reference.